Advancing Arabic Language Teaching and Learning : A Path to Reducing Learning Poverty in the Middle East and North Africa - Gregory, Laura; Taha Thomure, Hanada; Kazem, Amira; Boni, Anna; Elsayed, Mahmoud Abduh A.; Taibah, Nadia (World Bank, Washington, DC, 2021)
The purpose of the present report is to identify and explore the evidence on factors that are leading to high rates of learning poverty in MENA countries. In addition, the report proposes a path for countries of the region to make the teaching and learning of the Arabic language—which are critical foundations for children in Arabic-speaking countries—more effective. The intended audience of the report is education stakeholders in the MENA region, including officials in ministries of education across the region, those responsible for education decision-making, teachers, academics, education administrators, parents, and nongovernmental organizations, as well as World Bank and partner organization staff tasked with supporting countries in their efforts to raise learning and human capital.